Sucrose hydrolysis and phenolics production by Daucus Carota entrapped in hollow fiber reactors - Jose, Wilfredo I.; Pedersen, Henrik; Chin, Chee Kok.
Carrot cells immobilized in a hollow fiber membrane reactor were investigated for sucrose hydrolysis and formation of phenolics. The reactor system was run in batch, once-thru, and partial recycle configurations. The results showed that hollow fibers are suitable for plant cells, but since they are expensive and fragile, a modified system is proposed.
Keywords: Carrots; Sucrose hydrolysis